Problema das sequências justas ponderadas - Pessôa, Bruno Jefferson de Sousa (2017)
Scheduling problems on which constraints are imposed with regard to the temporal distances between successive executions of the same task have numerous applications, ranging from task scheduling in real-time systems to automobile production on a mixedmodel assembly line. This paper introduces a new NP-hard optimization problem belonging to this class of problems, namely the Weighted Fair Sequences Problem (WFSP). In addition to the study of the computational complexity of the WFSP, we present a mathematical formulation based on mixed-integer linear programming as well as a serie of cuts that improve the problem resolution via exact methods. To solve the WFSP, we propose an iterative method that greatly reduces the number of variables in the WFSP formulation and a heuristic solution developed from the combination of classical metaheuristics from the literature. Computational experiments show that, for a given time limit, the proposed approaches significantly increase the number of instances solved, preserving the quality of the solutions.